Review of The Fund's Income Position for FY 2022 and FY 2023-2024. - International Monetary Fund. Finance Dept.. (Washington, D.C. : International Monetary Fund, 2022)
This paper updates the projections of the Fund's income position for FY 2022 and FY 2023-2024 and proposes related decisions for the current financial year. The paper also includes a proposed decision to set the margin for the rate of charge for financial years 2023 and 2024.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution; Monetary Policy; Political Economy